Bahamas. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in the Bahamas during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as plant health, food security, public policies, resilience against climate change, trade, agribusiness, agroecotourism, permaculture, health and food safety, through the Codex Alimentarius, OIE, CIPF and WTO. Likewise, it was supported in the hardening of the crop tissue, in the handling of food through the ServSafe certification, in the implementation of projects, plans and strategies. Finally, work was done to include local producers, improve sheep and goat breeds, and the value chains of cassava, sweet potato, sheep, goats, pigs, poultry, and fishing.